Otimização de rotas tecnológicas de processamento e distribuição de resíduos municipais - Balcazar, Juan Galvarino Cerda [UNESP] (2014)
With the increase in population and industries, an increase in waste generation of various nature is observed. Domestic waste, industrial waste health service, among others, must be safely disposed. There are several ways to dispose the waste in a secure manner, such as controlled landfills, bio-digestion plants and incinerators, solutions that are used separately. By the other side, in recent decades a significant increase in power consumption was observed due to various factors, such as population growth and improved quality of life. In this research, an optimization model that encompasses the use of different technologies for energy generation and technological pathways for processing of waste through processes of thermal, biological and recyclable was analyzed. The model is applied in a case study for the metropolitan regions of São Paulo, Campinas and the Paraíba Valley and the North Coast just using consolidated technologies for waste processing. The results show a considerable production of electric energy even given to recycling and bio-stabilization. The heat treatment produces ash that can be used in industry or can be disposed of as landfill cover. The sale of raw materials produced by recycling and organic fertilizer technologies make this project financially attractive. The use of waste transportation improves efficiency, power generation and financial revenue. It also analyzes the advantages of a reduction in emissions of carbon equivalent, in which this difference can be commercialized. From the modeling performed, it was found that some regions should concentrate liquid and organic wastes to enhance the biogas generation in bio-stabilization waste technologies, enabling the increase of hybrid cycles, thereby improving the electric power processing plants. Electric energy, organic fertilizer, recycled matter and ash can be sold, ... (Complete abstract click eletronic access below)